Women and the United States Constitution : history, interpretation, and practice - Schwarzenbach, Sibyl A.; Smith, Patricia, 1956- (Columbia University Press, 2003)
Women and the U.S. Constitution is about much more than the nineteenth amendment. This provocative volume incorporates law, history, political theory, and philosophy to analyze the U.S. Constitution as a whole in relation to the rights and fate.